The Pitfalls of Relying Solely on Guidelines for Chronic Coronary Syndrome: A Warning for Cardiologists - Mulijono, Dasaad (Cardiology and Cardiovascular Medicine, 2025)
Guidelines play a crucial role in standardizing medical practice, particularly in the management of chronic coronary syndrome (CCS). However, strict adherence to symptom-based screening protocols may lead to missed diagnoses and fatal outcomes, as many patients suffer sudden cardiac events without warning symptoms. This article highlights the dangers of relying solely on guideline recommendations and advocates for a more proactive screening approach that considers family history, lifestyle, stress levels, and advanced imaging for subclinical atherosclerosis. Furthermore, it examines the legal and ethical risks associated with over-reliance on guidelines, emphasizing that courts may view rigid adherence as negligence if it disregards clinical judgment. As guidelines evolve, cardiologists must integrate structured recommendations with individualized risk assessments to ensure optimal patient care and prevent avoidable cardiac events.